Effect of chitosan-epigallocatechin gallate coating on volatile flavor compounds retention in bighead carp (Aristichthys nobilis) fillets during chilled storage. (1st November 2022) - Dai, Wangli; Wang, Wenjie; Gu, Saiqi; Xu, Mingjiang; Yao, Hongzheng; Zhou, Xuxia; Ding, Yuting
Abstract: The effects of chitosan-epigallocatechin gallate (EGCG) coating on sensory properties and retention of volatile flavor compounds (VFCs) in chilled bighead carp fillets were examined. Scores of odor and overall acceptability indicated that as compared with the control group and group coated with chitosan, chitosan-EGCG coating had the best retention effect on the flavor and quality of the fillets. Twenty-eight VFCs, mainly alcohols, ketones, and aldehydes, were identified from the fillets by GC-IMS analysis. Fillets in the control group showed unique characteristic VFCs distribution at different storage stages: 2-butanone in the early stage; 3-methylbutanal and 2-methylbutanal in the middle stage; and heptanal and 1-octen-3-ol in the final stage. However, the VFCs signals in chitosan-EGCG coated fillets were delayed along with the sharply suppressed intensities of off-odor VFCs such as 1-octen-3-ol, indicating that chitosan-EGCG coating was able to inhibit the formation of off-odors effectively. Principal component analysis and clustering analysis distinguished samples with different storage times and treatments. This study indicated that chitosan-EGCG coating could maintain the flavor quality of bighead carp fillets, and the characteristic VFCs of different storage stages could be considered as signal indicators to identify fish freshness. Graphical abstract: Image 1 Highlights: Chitosan-EGCG coating was conducive to the retention of natural flavor of fillets. Chitosan-EGCG coating significantly inhibited the formation of off-flavors. The fillets had unique characteristic VFCs distribution at different storage stages. Chitosan-EGCG coating was suggested as the preservative for bighead carp fillets.